Analysis Of Vibro-Acoustic Effect Of Micro-Perforated Panel Sound Absorber - Tan, Wei Hong (2013)
The application of micro-perforated panel (MPP) in the silencers and optimization of dual layer MPP sound absorber are evaluated in this study. MPP is a good candidate to be used in the silencer for achieving high transmission loss as it delivers high sound absorption performance. Boundary element method (BEM) in acoustical simulation has been used to assess the transmission loss performance of silencer attached with MPP, and when compared with the measurement using two-load method shows good agreement with the strong correlation coefficient, which is between 0.77 to 0.89. This verifies the BEM model of the silencer transmission loss analysis. For simple expansion chamber silencer, the application of MPP in the BEM model shows improvement in the transmission loss results with broader frequency bandwidth compared to the simple expansion chamber silencer without the MPP. The simulation work and analysis continues with the reflective system silencer and perforated tube silencer with MPP. The second part of this study is the optimization of the dual layer MPP sound absorber with consideration of the vibro-acoustic effect in which the classical plate equation is coupled to the acoustic wave equation. This is enhancing the sound absorption performance of an MPP sound absorber by taking the advantage of MPP plate vibration effect. The results of the vibro-acoustic model when applied to the single layer MPP, were found to be in good agreement with other published results.